Effects of Physical Activity and Ginkgo Biloba on Cognitive Function and Oxidative Stress Modulation in Ischemic Rats - Vaghef, Ladan; Bafandeh Gharamaleki, Hassan (International Journal of Angiology, 2017)
Either exercise or Ginkgo biloba is reported to improve cognitive functioning. The aim of this study is to compare the protective effects of forced exercise and Ginkgo biloba on oxidative stress as well as memory impairments induced by transient cerebral ischemia. Adult male Wistar rats were treated with treadmill running or Ginkgo biloba extract for 2 weeks before cerebral ischemia. Memory was assessed using a Morris water maze (MWM) task. At the end of the behavioral testing, oxidative stress biomarkers were evaluated in the hippocampus tissue. As expected, the cerebral ischemia induced memory impairment in the MWM task, and oxidative stress in the hippocampus. These effects were significantly prevented by treadmill running. Indeed, it ameliorated oxidative stress and memory deficits induced by ischemia. In contrast, Ginkgo biloba was not as effective as exercise in preventing ischemia-induced memory impairments. The results confirmed the neuroprotective effects of treadmill running on hippocampus-dependent memory.
Keywords: physical activity; Ginkgo biloba; transient cerebral ischemia; spatial memory; oxidative stress; hippocampus; rat